2023
DOI: 10.3390/ijms24043873
|View full text |Cite
|
Sign up to set email alerts
|

Second Generation of Antiepileptic Drugs and Oxidative Stress

Abstract: Epilepsy is a chronic disease of the central nervous system characterized by recurrent epileptic seizures. As a result of epileptic seizure or status epilepticus oxidants are excessively formed, which may be one of the causes of neuronal death. Given the role of oxidative stress in epileptogenesis, as well as the participation of this process in other neurological conditions, we decided to review the latest state of knowledge regarding the relationship between selected newer antiepileptic drugs (AEDs), also kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 92 publications
(214 reference statements)
0
2
0
Order By: Relevance
“…Moreover, LTG has also been shown to have antioxidant properties ( Table 2 ), which contribute to its neuroprotective effects by reducing oxidative stress and increasing cell viability [ 61 ]. Several studies have investigated the impact of LTG on oxidative stress, with malondialdehyde (MDA) levels and concentrations of glutathione (GSH), catalase (CAT), and superoxide dismutase (SOD) used as measures of stress intensity.…”
Section: Overview Of Antiepileptic Drugsmentioning
confidence: 99%
“…Moreover, LTG has also been shown to have antioxidant properties ( Table 2 ), which contribute to its neuroprotective effects by reducing oxidative stress and increasing cell viability [ 61 ]. Several studies have investigated the impact of LTG on oxidative stress, with malondialdehyde (MDA) levels and concentrations of glutathione (GSH), catalase (CAT), and superoxide dismutase (SOD) used as measures of stress intensity.…”
Section: Overview Of Antiepileptic Drugsmentioning
confidence: 99%
“…[84][85][86] Oxidative stress is considered as a possible mechanism in the pathogenesis of epilepsy and epileptogenesis, especially during aging and in conjunction with neuroinflammation. 14,[87][88][89] However, whether ion transport, and especially ion channels implicated in extracellular K + buffering could be a target of oxidative stress and provoke epilepsy during aging is largely unexplored.…”
Section: Kir21 Protein Trafficking To the Plasma Membrane Was Not Alt...mentioning
confidence: 99%
“…The most known side effects are diplopia, dizziness, ataxia and nausea and somnolence and rash. 9 However, a study found no evidence of the therapeutic role of LTG in neuropathic pain & fibromyalgia. 10 Fluvoxamine (FLX) is an antidepressant, functions as an inhibitor of reuptake of serotonin.…”
Section: Introductionmentioning
confidence: 99%